Experimental assessment of subgrade stiffness of lateritic soils treated with crushed waste plastics and ceramics for pavement foundation - Chibuzor Onyelowe, Kennedy; Bui Van, Duc; Nguyen Van, Manh; Ezugwu, Charles; Amhadi, Talal; Sosa, Felix; Wu, Wei; Ta Duc, Thinh; Orji, Francis; Alaneme, George (International Journal of Low-Carbon Technologies, 2019)
The assessment of subgrade stiffness of four test soils treated with crushed waste ceramics (CWC) and crushed waste plastics (CWP) has been experimented on under laboratory conditions. There have been recorded failures of pavements resulting from inadequate subgrade formations and the use of weak and expansive soils as subgrade materials. The changes in the behavior of these foundation materials affect the performance and overall behavior of the entire pavement or foundation structure. The aim of this work was to assess the behavior of test soils commonly used as subgrade materials and treat same with selected solid waste based geomaterials to enhance their ability to withstand dynamic and cyclic loads. The selected solid waste based geomaterials were crushed waste ceramic and crushed waste plastics. The test materials including the soils were tested for characterization procedure. The preliminary test results showed that the test soils were classified as A-2-7, A-2-6, A-7 and A-7-5, respectively according to AASHTO classification system and poorly graded soils according to USCS. They were also classified as highly plastic soils and expansive with plasticity indexes of above 17%. The oxide composition test on the CWC and CWP shows that the materials possess pozzolanic properties with high aluminosilicates. The test soils were treated with these geomaterials in the proportion of 10% to 120% by weight. The treatment protocol showed that the CBR, resilient modulus, and r-value improved consistently with increased CWC and CWP. Lateral deformation observed from the modified triaxial compression also reduced consistently with increased proportions of CWC and CWP. It is novel to have achieved improved California bearing ratio characteristics, resilient modulus, resistance value and lateral deformation properties of the test soils with a solid waste based geomaterial. It is also promising that beyond the proportion utilized in the laboratory, the CWC and CWP treated soils will resist both axial and lateral deformation or failure when compacted to the maximum dry density and optimum moisture.
Keywords: Subgrade stiffness; Crushed waste plastics; Crushed waste ceramics; Moisture bound materials; Recycled solid waste materials; Geomaterials